Reactive Solute Transport Through Two Contrasting Subterranean Estuary Exit Sites in the Ría de Vigo (NW Iberian Peninsula) - Calvo-Martin, Elisa; Álvarez-Salgado, Xosé Antón; Rocha, Carlos; Ibánhez, J. Severino Pino (Frontiers in Marine Science, 2021)
Subterranean estuaries (STEs), where continental groundwaters and saltwaters meet, are zones of intense biogeochemical reactivity. As such, STEs significantly modify groundwater-borne nutrient fluxes to the coastal zone. Thus, evaluating their reactive role is crucial to anticipate impacts of submarine groundwater discharge over coastal ecosystems. Here, we studied the nitrogen biogeochemistry of two STEs with contrasting wave-exposure and redox conditions in Panxón and Ladeira beaches (Ría de Vigo, NW Iberian Peninsula). Seasonal surveys were performed at the permanently saturated zone of both beaches during low tide in February, May, July and October 2019. Sediment was sampled and porewater samples collected using push-pull piezometers. Salinity, 222Rn and 226Ra activities were used to trace water circulation inside each beach. Porewater nitrate, ammonium, nitrite and dissolved oxygen were used to evaluate the role of these STEs as reactive sinks or sources of inorganic nitrogen. Our results showed a marked seasonal variability of water circulation inside both beaches, with strong salinity gradients in February and May and weakened circulation in July and October. The presence of a gravel layer in Panxón beach completely altered the typical structure of STEs by increasing porewater transport and mixing through the beach interior. As a result, Panxón beach profiles were highly enriched in nitrate and oxygen. Conversely, suboxic and anoxic conditions were prevalent in Ladeira beach during the study period, with ammonium being the prevailing inorganic nitrogen form. High nitrate concentrations occurred associated to the tidal circulation cell during February and May, being the only effective mechanism of sediment oxygenation in Ladeira beach. Although nitrate reduction and production were observed in both STEs, comparison with averaged conservative mixing porewater profiles showed that Ladeira beach acted as a net nitrogen sink whereas Panxón beach acted as a net nitrogen source. The presence of a gravel layer oxygenates the interior of Panxón beach, thus limiting nitrate reduction and promoting the amplification of groundwater-borne nitrogen fluxes to the coast.